La democratización del espectro radioeléctrico en el ecuador y su aporte a la creación de radios comunitarias en las parroquias rurales del sur del cantón Loja. Período marzo-julio 2014 - Armijos Macas, Gianella Patricia (2014)
This research entitled: "The democratization of the airwaves in Ecuador and its contribution to the establishment of community radio stations in the rural parishes Loja Canton South. March-July 2014 period, "evidence opening the Communications Act and applicable laws of the country for access to democratic and free communication of communities, peoples and nationalities of the country through the creation of equitable community media. In the development of the subject methods, materials, techniques and instruments that contributed to clarify the investigative work was used. With the results obtained from the methodology, more precisely in the implementation of the survey and interview were verified both the general and specific objective to demonstrate the expectations outlined in the research, also draw conclusions and recommendations of the research product. With all the fieldwork, an alternative proposed by analyzing the process of democratization of the airwaves in the construction of a community radio was formulated. Fundamentally the support of the inhabitants of the rural parishes in southern canton of Loja and relevant authorities on the subject, provided the elements necessary for building up the research process. Once known, analyzed and synthesized the problem, the creation of the communication project for the implementation of a community radio station that benefits five rural parishes Canton South Loja intends, "Voice of the South" will be called and will be administered by the presidents of the Parish Government.